A Comparison of Vaccination Policies and Immunity Assessment for Measles Control: Insights from the United States and Japan - Naruhito Otani; Toshiomi Okuno; Toshie Tsuchida; Kaori Ishikawa; Kaoru Ichiki; Takashi Ueda; Satoshi Higasa; Kazuhiko Nakajima (Viruses)
Measles is a highly contagious viral disease and remains a global health challenge despite the availability of effective vaccines. Although many regions have successfully eliminated measles, outbreaks continue to occur owing to vaccine hesitancy, inadequate coverage, and imported cases. Differences in epidemiology, vaccination policies, and immunity assessment influence measles control across countries. This paper compares measles epidemiology, vaccination policies, and immunity assessment approaches in the United States and Japan. Data were obtained from surveillance reports, national immunization programs, and peer-reviewed literature. The introduction of the measles vaccine led to substantial reductions in incidence. The United States eliminated measles in 2000 but continues to experience outbreaks due to vaccine hesitancy and imported cases. Japan implemented a two-dose policy in 2006, reducing case numbers; however, sporadic outbreaks among adults persist. In the United States, immunity is primarily assessed using documented vaccination history, whereas in Japan, enzyme immunoassay is commonly used to evaluate immunity status. Despite progress in measles elimination, achieving high vaccination coverage and addressing vaccine hesitancy remain critical challenges. Variations in immunity assessment methods impact surveillance accuracy and outbreak control. Strengthening international collaboration, standardizing assessment protocols, and enhancing public health education are crucial for sustained measles elimination.